สุขภาพจิตของนิสิตหญิงหลังปริญญาผู้ใช้เฟซบุ๊ก - สุดารัตน์ จ๊ะถา (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purpose of this cross-sectional descriptive study was to determine mental health in female postgraduate students who were Facebook users. The subjects were 112 female postgraduate students at Suksit Nives international house who used Facebook. Research instruments included 4 self-report questionnaires: a questionnaire on general background, a questionnaire on patterns of Facebook use, the Facebook- Addiction Questionnaire (Thai version) and the Thai Mental Health Indicators Version 2007 (TMHI-55). Statistical analyses included descriptive statistics, independent-sample T-test, one-way ANOVA, Fisher s Exact Test and multiple linear regression analysis. The result showed that the mean age of the sample was 27 years (x̄=26.92). Most were studying for the Master’s degree in Science, with the average GPA of 3.78. Most were single, had income of less than 15,000 bath, had good relationship with friends and family. Regarding Facebook using, the average time spent online was 6 hours (x̄=6.02) per day. Most had registered for Facebook for more than 3 years and had 385 Facebook friends (x̄=384.25). According to the Facebook- Addiction Questionnaire (Thai version) 25.9% of the overall sample were Facebook-Addicted. Using the TMHI-55 it was found that the mean mental health score of the sample was 170.96 which was in a normal range. From Multiple Regression Analysis, a model which predicted the mental health of the sample with a predicative value of 76.4 % included age, Facebook account duration (over 3 years), marital status (married), peer relationship (not good), family relationship (good), Facebook addiction, Facebook use period (4hrs or more/day) Online period (4hrs or more/day), fields of study (social sciences), and income(less than 15,000).